Perancangan Sistem Informasi Pengendalian Persediaan Barang Produksi pada PT. Harmonics Techindo Agung - Basri, Hasan; Devi Alisa Putri; Alif Rizqi Mulyawan; Salman Alfarizi; Nurul Ichsan (PROFITABILITAS, 2025)
Information technology that is very important for an agency and company can be used to facilitate a job in achieving goals optimally. PT. Harmonics Techindo Agung is a company engaged in the manufacturing industry, Designing an information system for controlling production goods inventory at PT. Harmonics Techindo Agung is done because the system used is still done manually which results in data being easily lost, a long time in data processing, and frequent errors in data input. To overcome this, researchers use the Prototype method in the process of controlling production goods inventory at PT. Harmonics Techindo Agung to help software development in creating software models that provide an idea of ideas, experimenting with designs so that they can provide convenience for companies in managing data faster, more accurately and effectively.